HYPOGLYCEMIC AND HYPOLIPIDEMIC EFFECT OF SALVADORA OLEOIDES IN NORMAL AND ALLOXAN-INDUCED DIABETIC RATS - Yadav, J. P.; Saini, S. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Diabetes mellitus is a heterogeneous primary disorder of the carbohydrate metabolism with multiple etiological factors that generally involve absolute or relative insulin deficiency or insulin resistance or both. All causes of diabetes ultimately lead to hyperglycemia, which is the landmark of this disease syndrome. Salvadora oleoides Decne. (Salvadoraceae family) commonly known, as meetha jal is an oil yielding medicinal and multipurpose tree. It is adaptable to arid and alkaline conditions. Leaves of Salvadora oleoides are used to relieve cough, employed in the treatment of enlarged spleens and low fevers. Leaves of Salvadora oleoides have been mentioned to possess anti-inflammatory, analgesic and antiulcer activity. The objective of the present study was to evaluate the hypoglycemic and hypolipidemic activity of an ethanolic extract of aerial parts (stem and leaves) of Salvadora oleoides in normal and alloxan induced diabetic rats. Diabetes was induced in albino rats by administration of alloxan monohydrate (120 mg/kg i.p.). Normal as well as diabetic albino rats were divided into groups (n=6) receiving different treatments consisting of the vehicle (control), the ethanolic extract (1 g and 2 g/kg b.w) and the standard antidiabetic drug tolbutamide (0.5 g/kg b.w.). Blood samples were withdrawn by cardiac puncture and were analysed for blood glucose and lipid profile on day 0, day 7, day 14, and day 21. The ethanolic extract of Salvadora oleoides showed significant reduction (P<0.001) in blood glucose and also produced beneficial effects (P<0.001) on the lipid profile in euglycemic as well as alloxan induced diabetic rats at the end of the treatment period (21st day). It is concluded that the ethanolic extract of Salvadora oleoides is effective in controlling blood glucose levels and improves lipid profiles in euglycemic as well as diabetic rats. Hence further study on active principles of Salvadora oleoides may provide a better solution for million of diabetics. The lowering effect of TG, TC, LDL, VLDL will lead to the decrease of coronary heart disease (CHD) and an increase in the HDL level, which is known to be a protective factor in CHD.